Studi Pengembangan Buah Jamblang (Syzygium Cumini L.) Menjadi Minuman Fungsional Kaya Antioksidan - Rais M; Irmayani Irmayani; A. Hermina Julyaningsih (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
Coppeng is the term given by the Bugis/Makassar people to define Java Plum fruit. This fruit is a seasonal fruit that is rich in antioxidants because it contains high levels of vitamin C and anthocyanins. Due to the high antioxidant content of the java plum fruit, this fruit has many benefits that are good for health, but it turns out that this fruit is not liked by the public because of its sour and astringent taste and its properties that cannot be found all year round in the market. One of the efforts to increase the utilization of java plum fruit can be done by processing this fruit into other processed products such as functional drinks, but it is necessary to do research first regarding the determination of the formulation between the comparison of the use of java plum fruit juice, water and sweetener (fructose/sucrose). Java Plum juice was made by mixing pure fruit juice and water in a ratio of 40:60, 50:50, and 60:40, then adding 15% sweetener according to treatment (fructose/sucrose). Java plum drinks that have been prepared are tested chemically including testing for total acid, vitamin C content, pH, anthocyanin content, and antioxidants, and also through organoleptic testing including taste, aroma, and color of java plum juice. The results of the chemical analysis showed that fruit drinks with a ratio of pure fruit juice and water 60:40 and using sucrose had the highest total anthocyanins compared to other treatments. Fruit juice with a ratio of pure fruit juice and water 60:40 with the addition of fructose had the highest vitamin C content and total acid compared to other treatments, so this also caused this treatment to have the smallest pH value. The results of the organoleptic analysis showed that the ratio of pure fruit juice and water of 50:50 with the addition of sucrose was the most preferred by the panelists in terms of taste, while the ratio of 60:40 with the addition of fructose was preferred by the panelists in terms of color and aroma.